A Dictionary of Vurës, Vanuatu - Malau, Catriona (Asia-Pacific Linguistics, 2021)
This is a trilingual dictionary of Vurës, with meanings provided in both English and Bislama, the national language of Vanuatu. Vurës is an Oceanic language spoken on the island of Vanua Lava in Vanuatu. The dictionary is a companion volume to A Grammar of Vurës, Vanuatu (Malau 2016). There is no established tradition of writing in Vurës and most speakers are not literate in their own language. This dictionary is intended to have a dual purpose: to support the learning of literacy skills in the Vurës community, and as a reference work for linguists. There are four parts to the dictionary. The main part is the most comprehensive and provides the English and Bislama definitions of Vurës words, as well as example sentences for many of the entries, additional encyclopaedic information, scientific names for identified species, lexical relations, and etymological information for some entries. The dictionary contains approximately 3,500 headwords and has a strong emphasis on flora and fauna with close to a third of the entries belonging to these semantic domains. The dictionary has benefited from collaboration with a marine biologist and botanists, who have provided scientific identifications for named species. The main dictionary is followed by English-Vurës and Bislama-Vurës finderlists. The final part of the dictionary is a thesaurus, in which Vurës words are grouped according to semantic categories. The thesaurus has been included primarily so that it can be used to support teaching of literacy skills and cultural knowledge within the community.